1987
DOI: 10.5642/aliso.19871104.08
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Numbers and Evolution in Anoda and Periptera (Malvaceae)

Abstract: A BSTRACTRelationships within and between the principally North American, malvaceous genera A noda and Periptera are assessed through analysis of chromosomal and hybridization data. Chromosome numbers are reported for ten species of Anoda and one of Periptera, and observations on meiosis in hybrid and non hybrid plants are presented . The results indicate: I) that Anoda and Periptera are closely related and occupy a relatively isolated position in the tribe Malveae, 2) that speciation in A noda has occurred pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(14 reference statements)
0
4
0
2
Order By: Relevance
“…Anoda cristata is the most morphologically variable species within the Anoda genus (Bates, 1987), and seed weight is lower in most populations in the United States (Van Gessel et al ., 1998) compared with the present study in Argentina. However, within the study population, seed weight was a conservative trait and did not differ between cohorts and planting patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Anoda cristata is the most morphologically variable species within the Anoda genus (Bates, 1987), and seed weight is lower in most populations in the United States (Van Gessel et al ., 1998) compared with the present study in Argentina. However, within the study population, seed weight was a conservative trait and did not differ between cohorts and planting patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Only one alliance (Anoda) is monophyletic based on the ITS data. Anoda and Periptera were suggested to be closely related (Bates, 1987;Fryxell, 1997); both genera possess ephemeral mericarp walls (also found in Cristaria, to which they are not closely related) and are primarily distributed in Mexico. Periptera (only one species counted) has a haploid chromosome number of n ϭ 13, while Anoda is more chromosomally diverse with n ϭ 13, 14, 15, 18, 30, or 45 (Bates, 1987;Fryxell, 1997).…”
Section: Alliances and Genera Of Clade A-as Mentioned Cladementioning
confidence: 99%
“…Periptera (only one species counted) has a haploid chromosome number of n ϭ 13, while Anoda is more chromosomally diverse with n ϭ 13, 14, 15, 18, 30, or 45 (Bates, 1987;Fryxell, 1997). Interestingly, Bates (1987) noted that the only n ϭ 13 species of [Vol. 92 AMERICAN JOURNAL OF BOTANY Anoda (A. thurberi) forms a very robust hybrid (in greenhouse crosses) with Periptera punicea (n ϭ 13) and that these may represent a lineage derived within Anoda.…”
Section: Alliances and Genera Of Clade A-as Mentioned Cladementioning
confidence: 99%
“…The New Mexico accession was most variable in terms of plant and leaf morphology. Spurred anoda is the most morphologically variable species within the Anoda genus (Bates 1987). Fryxell (1987) indicated that leaf morphology is characteristically very different within individuals of Anoda.…”
Section: Plant Morphologymentioning
confidence: 99%